1964
DOI: 10.1136/gut.5.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation between Urecholine and gastrin extract and between Urecholine and histamine in the stimulations of Heidenhain pouches

Abstract: EDITORIAL SYNOPSIS These studies clearly establish the existence of true potentiation between Urecholine and gastrin and between Urecholine and histamine in stimulating secretion both of acid and of pepsin.It is frequently said that cholinergic activity, induced either by drugs or by vagal activity, 'potentiates' the acid secretory responses to gastrin or to histamine. The assumption that these combinations of stimuli act in a 'potentiated' rather than an 'additive' fashion is based upon the large augmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 7 publications
4
32
0
Order By: Relevance
“…Furthermore the presence of phosphodiesterase inhibition by IMX did not alter these findings with carbamylcholine and gastrin. It (16,(21)(22)(23)(24)(25); however, interactions demonstrated in this manner are species dependent and variable in magnitude (15,(26)(27)(28). A dramatic demonstration of secretagogue interactions has been made in studies with the ex vivo canine stomach preparation where marked potentiation was found between histamine and pentagastrin, between histamine and bethanechol, and between pentagastrin and bethanechol (29,30).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore the presence of phosphodiesterase inhibition by IMX did not alter these findings with carbamylcholine and gastrin. It (16,(21)(22)(23)(24)(25); however, interactions demonstrated in this manner are species dependent and variable in magnitude (15,(26)(27)(28). A dramatic demonstration of secretagogue interactions has been made in studies with the ex vivo canine stomach preparation where marked potentiation was found between histamine and pentagastrin, between histamine and bethanechol, and between pentagastrin and bethanechol (29,30).…”
Section: Discussionmentioning
confidence: 98%
“…After 1 hour the dose of the stimulant was doubled, followed by successive doublings of the dose each hour until the secretory rate no longer increased with increments in drug dosage (maximal response). At this point bethanechol (0.5 mg) was infused for 1 hour, along with the maximal dose of histamine or gastrin, to induce a supramaximal secretory response (15). In some experiments a steady submaximal secretory response was maintained with histamine or gastrin, and a secretory inhibitory agent (vasopressin, epinephrine, isoproterenol, or secretin) was added to observe the effect of these agents on both secretion and clearance.…”
Section: Methodsmentioning
confidence: 99%
“…Studies concerning the potentiation between gastric acid secretary stimulants have been made principally in the dog (Brooks, Johnson & Grossman, 1970;Gillespie & Grossman, 1964; Olbe, 1964; Passaro, Gillespie & Grossman, 1963) and in man (Brooks et al 1970;Konturek & Oleksy, 1967;Makhlouf, McManus & Knill, 1968). As the rat is convenient to use in the study of gastric secretion it is desirable to obtain fundamental information concerning the acid secretary process in this species.…”
Section: Introductionmentioning
confidence: 99%